Apriori Algorithm and Business Intelligence Methods for Bookstore’s Customer Preferences Analysis - Ramadhan, Silmy Kafi; Septiani, Devi; Rahman, Afida; Handayani, Endah Tri Esti (Lumina Infinity Academy Foundation, 2025)
This study explores the use of a priori algorithm in analyzing sales transaction data at Rony Jaya Bookstore. By combining data mining and business intelligence, the study successfully uncovered significant customer buying patterns, which were then used to support strategic decision-making. The results of the analysis showed that there was a close relationship between certain book categories, such as Fiction Books and Educational Books with a confidence level of 87.5%, as well as Non-Fiction Books and Educational Books with a confidence level of 88.89%. These findings provide valuable insights into developing marketing strategies, such as creating custom promotional packages and arranging product layouts in stores to make them more appealing to customers. This research also highlights the importance of ensuring data quality so that the resulting analysis is more accurate and relevant. Overall, the study offers a practical guide for Rony Jaya Bookstore and other businesses looking to leverage data mining and business intelligence technologies to improve efficiency and customer satisfaction.